Konsep Kebebasan dalam Novel Pasung Jiwa Karya Okky Madasari : Analisis Filsafat Eksistensialisme Soren Kierkegaard - Ardiansyah, Bagus; Maraimbang, Maraimbang; Utomo, Wahyu Wiji (AHKAM, 2023)
Literature and philosophy are like two sides of a coin that cannot be separated from each other. There is even a reciprocal relationship between literature and philosophy. It can be proven that the birth of a literary work is the author's philosophical reflection on the reality he faces. raises various problems related to mental health and the stigma that still exists in society and the research problem that will be identified in this thesis is the concept of freedom in the novel "Pasung Jiwa" by Okky Madasari with an analysis of Soren Kierkegaard's existentialist philosophy. The research objective was set to examine the concept of freedom in literature, Kierkegaard's thoughts about human existence, freedom, personal responsibility, and the meaning of life, as well as the relationship between the concept of freedom in literature and Kierkegaard's thought. The research method used is a qualitative method with textual analysis. By using qualitative methods and textual analysis, this research is expected to provide a comprehensive understanding of the concept of freedom in the novel and its relevance to Soren Kierkegaard's existentialist thought. It is hoped that the results of this research will provide a deeper understanding of the concept of freedom in literature and the contribution of Kierkegaard's thought to the writing and interpretation of literary work.